The extremely efficient and luminous-thermal-stable red phosphor based on new layered and rigid phosphate - Rong-Rong Wang; Jing Zhang; Yi-Jia Liu; Gui-Hua Li; Ge-Mei Cai (Materials Today Advances)
Developing idea red phosphors with high quantum efficiency and excellent fluorescent thermal stability has special significance for both lighting and display devices but is still challenging. The internal quantum efficiency of Eu3+ in reported red phosphors is generally few lower. The host takes a key role in offering special crystal local environment to Eu3+. In this work, inherent layered CaIn2(P2O7)2 (CIP124) phosphate with different M1 and M2 sites for Ca/In co-occupying was discovered. By introducing Eu3+ into CIP124, high quality red light has been successfully achieved. Eu3+ locates two positions simultaneously but prefers the symmetrically lower M2 site. The large interlayer distance reduced the possibility of effective energy capture by the quenching center thus achieved the high doping concentration of Eu3+. Structural refinement, vacuum-ultraviolet spectroscopy and Judd-Ofelt theory shed light on the low symmetry and stiffer environment of Eu3+ in CIP124. CIP124: 0.2Eu3+ shows extremely high internal quantum efficiency (99.9 %), satisfactory color purity (93.1 %), and outstanding luminous thermal stability with the emission intensity keeping 97.8 % of initial intensity at 423 K, superior to other reported red phosphors. Based on the newly developed red phosphor, an excellent white light-emitting diode (WLED) was self-fabricated. These results imply that CI1-xP124: xEu3+ phosphors can be used as the red component of phosphor converted WLEDs. This work proposed a new host with the layered host structure and rigid local environment which is beneficial for achieving phosphors with the superb luminous comprehensive performance.